Economic Value of Tourism in Bunaken Island based on Travel Cost Method - Lalenoh, Anna Maria; Pratasik, Silverter B.; Rembet, Unstain N. W. J.; Suhaeni, Siti; Moningkey, Ruddy D. (Jurnal Ilmiah Platax, 2021)
The objective of the study was to obtain the economic value of tourism in Bunaken Island. It employed Travel Cost Method (TCM), the expenses spent by the visitors from their house to Bunaken Island and during their stay on the island. Questioneers were used as a data collection tool. There were 100 respodents selected using accidental sampling and purposssive sampling. Data analysis applied travel costs of the visitors to Bunaken Island. Results revealed that total economic value based on the total travel costs of IDR. 147.875.000 with an average of IDR. 1.478.750/pers. was IDR. 257.262.425.875. This value is expected to be able to give significant contribution to the social-economic development to Bunaken Island communities, Manado, North Sulawesi.Keywords:Â  Tourism; expense; economic contribution; community. AbstrakTujuan penelitian adalah untuk mendapatkan nilai ekonomi wisata di Pulau Bunaken. Penelitian ini menggunakan Travel Cost Method (TCM), yaitu biaya yang dikeluarkan oleh pengunjung dari tempat tinggal dan selama berada di Pulau Buanken. Kuesioner digunakan sebagai alat pengumpul. Data 100 orang responden yang dipilih menggunakan accidental sampling dan purpossive sampling. Pengolahan data menggunakan biaya perjalanan responden ke Pulau Bunaken. Hasil menujukkan bahwa total nilai ekonomi berdasarkan total biaya perjalanan sebesar Rp. 147.875.000 dengan rata-rata biaya perjalanan sebesar Rp. 1.478.750/orang, sehingga total nilai ekonomi Pulau Bunaken adalah sebesar Rp. 257.262.425.875. Nilai ini diharapkan akan memberikan efek yang signifikan bagi pertumbuhan sosial ekonomi khususnya masyarakat Pulau Bunaken, masyarakat Kota Manado dan provinsi Sulawesi Utara.Kata kunci: Pariwisata; biaya; kontribusi ekonomi; masyarakat.